Pengembangan Materi Pembelajaran Praktikum Perbankan Syariah dalam Pendidikan Life Skill di Pesantren Ar-Risalah Cariu Bogor - Ranam, Sanudin; Syarif, Marhamah; Rosyid, Hamdan (Universitas Indraprasta PGRI Jakarta, 2024)
With the growing development of the sharia banking industry, especially in Indonesia, it is important for Islamic boarding schools to introduce sharia banking practicum to students as part of Islamic education. The Ar-Risalah Islamic Boarding School Cariu Bogor introduces sharia banking practicum learning materials as part of its curriculum to help students develop their skills and character in Islamic financial management. This research aims to develop and implement sharia banking practicum learning materials in Life Skills education at the Ar-Risalah Cariu Islamic Boarding School, Bogor. The ADDIE (Analysis, Design, Development, Implementation, Evaluation) model development approach was used in this research. Data was collected through observation, interviews and documentation. Data analysis was carried out using qualitative descriptive analysis techniques. The research was conducted from January to July 2023. Research results. The sharia banking practicum learning materials developed includes sharia banking principles, sharia banking products, and procedures in sharia banking transactions. Students are also taught how to make financial plans and manage finances in an Islamic way. Research shows that sharia banking practicum learning materials have been successfully developed and implemented well in Life Skills education at the Ar-Risalah Cariu Bogor Islamic Boarding School.